Design of a heat pipe for spacecraft cooling - Mesbah M. Salem; A. M. Elmabruk (African Journal of Advanced Pure and Applied Sciences, 2025)
This study presents a comprehensive design and performance evaluation of a heat pipe system intended for spacecraft thermal regulation under extreme environmental conditions. Utilizing the principles of thermodynamics, fluid dynamics, and heat transfer, the proposed design incorporates ammonia as the working fluid and employs an aluminum container with a stainless-steel wick structure. The design methodology addresses critical performance constraints such as capillary, boiling, sonic, viscous, and entrainment limits, ensuring reliable operation in microgravity. Analytical modeling and thermal resistance calculations were performed to assess heat transport capacity and temperature distribution across the pipe. The design achieves a minimum heat transfer rate of 15 W over a 1-meter pipe length, maintaining temperature control between 0 °C and 80 °C. Practical considerations related to material compatibility, structural integrity, and geometric limitations were also examined. The results confirm that the proposed heat pipe configuration satisfies the thermal management requirements for satellite applications and offers a lightweight, efficient, and reliable solution for spaceborne systems.